Scenario-Agnostic Localization System for Cellular Network Based on Feature Engineering - Luo Chen, Hao Qiang; Khatib, Emil Jatib; Sethi, Deepak; Cruz, Eduardo; Arostegui, Asier; Martín, Raúl; Barco-Moreno, Raquel (IEEE, 2024)
In the last few years, location-aware services and network management have driven the demand for user location estimation in mobile networks. Nevertheless, the location obtained from user terminals is not usually accessible to mobile operators. In addition, available cell Key Performance Indicators (KPI) vary highly from network to network, and only a few of them are always enabled widely. Currently prevalent Machine Learning (ML) based solutions have achieved high precision, but they are bound to a trained scenario, restricting their application to new areas. We propose a method for creating scenario-agnostic prediction models which solves these problems through applying feature engineering, over a small set of easily obtainable KPIs, applicable for any ML method. Finally, the performance of the proposed method is demonstrated using real network datasets.
Keywords: Sistemas de comunicaciones móviles; User location; Mobile network; RSRP; Generic model; Relative coordinates